Threats to Conservation of Vitellaria paradoxa subsp. nilotica (Shea Butter) Tree in Nakasongola district, Central Uganda - Buyinza, Joel; Okullo, John B. L. (International Research Journal of Environment Sciences, 2015)
This study assessed the major threats to conservation of the shea butter tree (Vitellaria paradoxa) on farms in Buruli subregion. Data were collected through a household survey, focused group and key informant interviews. Questionnaires data were coded, entered in Statistical Package for Social Scientists (SPSS) computer program and analyzed for major threats to conservation of the shea butter tree in Nakasongola District. Binary logistic regression analysis was used to show how socio- demographic characteristics influenced the willingness of the local people to protect shea butter trees on their farms. While the tree is a source of fruit, oil and charcoal to local communities, factors such as existing tree and land tenure system, termites, lack of planting materials and high poverty levels constrain on-farm shea tree growing. There was a significant association between marital status and willingness of the respondents to plant shea trees (R=6.614, P<0.05). The existing shea tree populations are entirely wild with great economic potential that needs to be conserved. Regional research programs should aim at mobilizing local communities to carry out interventions such as shea tree germplasm multiplication, assisted tree regeneration and encouraging farmers to protect naturally regenerating trees. This will enhance tree based rehabilitation of the degraded resources, while ensuring environmental sustainability and improved livelihoods. National governments and local and international conservation bodies need to come up with appropriate incentives for promoting on-farm conservation of this very valuable species. Efforts are also needed to propagate shea tree vegetatively and using seed. Failure to intervene will otherwise culminate into complete degradation and loss of shea parkland benefits, leading to ‘the tragedy of the commons’ not only in Buruli sub region, but also other shea parklands areas in Lango, Teso and West Nile sub regions of Uganda.
Keywords: Shea butter; drylands; conservation; threats.